(ii) The role of imaging in follow-up of newly introduced implants - Gill, H; Mellon, S; Pegg, E; Ostlere, S; Pandit, H; Murray, D (Elsevier, 2012)
A wide variety of orthopaedic implants is in clinical use and many new devices are brought to the market each year. The vast majority of these devices have no published clinical data. The concept of phased introduction has been developed. The use of radiostereometry and cross-sectional imaging in the follow-up and phased introduction of new orthopaedic implants is discussed.